NEUROSCIENCE, ATTENTIONAL CONNECTOME, AND INTELLIGENT TECHNOLOGIES IN THE EDUCATIONAL CONTEXT - Matias, Amanda Gilvani Cordeiro; Dorotea, Nuno Miguel Taborda Cid (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
Cognitive neuroscience and artificial intelligence form a rapidly expanding convergence for understanding neural and mental mechanisms and developing systems applicable to education. Neuroscience studies the brain as the core of learning, while technologies develop computational codes and simulate human cognitive functions. Attention is the central axis for other cognitions for knowledge acquisition and learning. Objective: to describe the fundamentals of attentional cognitive neuroscience and its convergence with technologies in the educational context. Methods: This is a scoping review with a three-year time frame, conducted in the SciELO, NCBI/PubMed®, and Science Direct databases, guided by the PCC (Population, Context, Concept) mnemonic strategy for formulating the guiding question and by the PRISMA-ScR checklist. Results: Twenty-eight articles met the research criteria. Convergences and advances in educational technologies were observed, with effects on attentional cognition that optimize concentration and personalization of learning. Considerations: The synergy between neuroscience and technologies drives educational transformations, considering the potential of the brain as the organ of learning.